In Salt Affected Soils Agroforestry is a promising option - Sharma, D. K.; Chaudhari, S.K.; Singh, Anshuman (Indian Farming, 2015)
Due to the global efforts in research and development in recent past, the age-old forms of agroforestry are becoming an integrated approach for addressing many of the world’s most serious landmanagement challenges. Development of diversified, climate resilient and farmer centric agroforestry systems has tremendous potential to significantly improve the sustainability of agro-ecosystems in salt-affected areas bringing tangible socio-economic and environmental benefits to the society and nation.